Cellular Fatty Acid Composition and Identification of Rumen Bacteria - Ifkovits, R. W. (1968)
The fatty acid compositions of 21 pure cultures of rumen bacteria, representing 12 genera and 14 species, were compared as methyl esters. Each organism possessed a consistent and reproducible fatty acid profile. Overlapping similarities and differences in composition did not allow differentiation between families or genera. Although species differentiation was possible, fatty acid composition appeared to be only an aid in the identification of bacteria.